The Impact of Laboratory Practical Activities on Students’ Academic Performance at Queen of Peace Senior High School in The Nadowli-Kaleo District of The Upper West Region of Ghana (International Journal of Scientific Research and Management (IJSRM), 2023)
The study looked at how Form Two (2) science students’ academic achievement in biology was affected by their biology practical. It was an action research study. For the study, Form Two (2) science students from Queen of Peace Senior High School were sampled. 42 students were surveyed using a Likert scale questionnaire, in addition to an interview and pre- and post-intervention test items. Descriptive statistics and the Statistical Package for Social Sciences (SPSS) were employed in the study to examine the findings. The study found that a lack of sufficient Science Resource Center equipment to support teaching and learning is to blame for students’ poor performance in biology. Despite this, the school’s biology teachers lacked proper training and there was no biology lab. Therefore, as a temporary fix to the issue, the study advised schools lacking the science resource centre to send students to schools with the amenities. Ghana Education Service (GES) and the Ghana Association of Science Teachers (GAST) should regularly hold in-service training workshops and courses to keep science teachers’ understanding on how to plan practical lessons current. According to the report, Ghana’s government should focus on providing the Science Resource Center facilities to all of the nation’s schools.